Laparoscopic surgery for gallstones or common bile duct stones: A stably safe and feasible surgical strategy for patients with a history of upper abdominal surgery - Yang, Shaojie; Wu, Shuodong; Dai, Wanlin; Pang, Liwei; Xie, Yaofeng; Ren, Tengqi; Zhang, Xiaolin; Bi, Shiyuan; Zheng, Yuting; Wang, Jingnan; Sun, Yang; Zheng, Zhuyuan; et al. (Frontiers in Surgery, 2022)
Backgrounds/Aims A history of upper abdominal surgery has been identified as a relative contraindication for laparoscopy. This study aimed to compare the clinical efficacy and safety of laparoscopic cholecystectomy (LC) and laparoscopic common bile duct exploration (LCBDE) in patients with and without previous upper abdominal surgery. Methods In total, 131 patients with previous upper abdominal surgery and 64 without upper abdominal surgery underwent LC or LCBDE between September 2017 and September 2021 at the Shengjing Hospital of China Medical University. Patients with previous upper abdominal surgery were divided into four groups: group A included patients with previous right upper abdominal surgery who underwent LC (n = 17), group B included patients with previous other upper abdominal surgery who underwent LC (n = 66), group C included patients with previous right upper abdominal surgery who underwent LCBDE (n = 30), and group D included patients with previous other upper abdominal surgery who underwent LCBDE (n = 18). Patient demographics and perioperative outcomes were retrospectively analyzed. Results The preoperative liver function indexes showed no significant difference between the observation and control groups. For patients who underwent LC, groups A and B had more abdominal adhesions than the control group. One case was converted to open surgery in each of groups A and B. There was no statistical difference in operation time, estimated blood loss, postoperative hospital stay, and drainage volume. For patients who underwent LCBDE, groups C and D had more estimated blood loss than the control group (group C, 41.33 ± 50.84 vs. 18.97 ± 13.12 ml, p = 0.026; group D, 66.11 ± 87.46 vs. 18.97 ± 13.12 ml, p = 0.036). Compared with the control group, group C exhibited longer operative time (173.87 ± 60.91 vs. 138.38 ± 57.38 min, p = 0.025), higher drainage volume (296.83 ± 282.97 vs. 150.83 ± 127.04 ml, p = 0.015), and longer postoperative hospital stay (7.97 ± 3.68 vs. 6.17 ± 1.63 days, p = 0.021). There was no mortality in all groups. Conclusions LC or LCBDE is a safe and feasible procedure for experienced laparoscopic surgeons to perform on patients with previous upper abdominal surgery.